Echocardiographic Findings in Ischemic Stroke Patients with Obstructive Sleep Apnea - Svatikova, Anna (2011)
BACKGROUND: Obstructive sleep apnea (OSA) has been associated with cardiac abnormalities. Whether any cardiac dysfunction is present in ischemic stroke patients with OSA is not known. The purpose of this study was to compare echocardiographic findings in ischemic stroke patients with and without OSA. METHODS: Nocturnal polysomnography was performed on 28 ischemic stroke subjects within 7 days of symptom onset. OSA was defined as an apnea-hypopnea index of ≥ 10. Echocardiographic variables were compared between the OSA and non OSA groups using Wilcoxon signed-rank, chi-square, or Fisher’s exact tests. RESULTS: The 14 (50%) subjects with OSA had comparable cardiac function and structure to those without OSA (n=14). Left ventricular (LV) mass index, LV ejection fraction, LV diastolic function, left atrial area, and right ventricular systolic function were not different between groups. Ischemic stroke subjects, regardless of their OSA status, had LV diastolic dysfunction with preserved systolic function. CONCLUSIONS: Subjects with and without OSA, based on polysomnography in the first 7 days after stroke, have comparable right and left ventricular function.